The Effect of STEM Curriculum Based on Islamic Perspective on 9th Grade Talented Female Students' Critical Thinking in Gaza - Al-Hidabi, Dawood Abdulmalek Yahya; Abu Owda, Mohammed F. (2019)
The study aimed to uncover the effect of using a Developed Science Curriculum Based on STEM approach with Islamic Perspective on Improving Critical Thinking Skills among 9th Grade Talented female students in Gaza. To achieve the study objectives, the two researchers analyzed the content "Human body organs" in science course to the ninth grade in the light of critical thinking skills, as its shown that critical thinking skills which are available in the unit are conclusion, deduction, interpretation, Arguments evaluation, and hypotheses. The researchers used the quasi-experimental approach. The study used critical thinking skills test as tool. The study was conducted on 21 female 9th grade talented students in west Gaza Directorate. Results of the study showed statistically significant differences at significance level (α = 0.01) between the average scores of the critical thinking skills of the experimental group in the pre/post application of critical thinking skills test. In addition, the results showed differences in the post application in all critical thinking skills, and that thea Developed Science Curriculum Based on STEM approach with Islamic Perspective has a significant impact (ƞ² = 0.61).